If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5w + -19 = -6(w + 5) Reorder the terms: -19 + 5w = -6(w + 5) Reorder the terms: -19 + 5w = -6(5 + w) -19 + 5w = (5 * -6 + w * -6) -19 + 5w = (-30 + -6w) Solving -19 + 5w = -30 + -6w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '6w' to each side of the equation. -19 + 5w + 6w = -30 + -6w + 6w Combine like terms: 5w + 6w = 11w -19 + 11w = -30 + -6w + 6w Combine like terms: -6w + 6w = 0 -19 + 11w = -30 + 0 -19 + 11w = -30 Add '19' to each side of the equation. -19 + 19 + 11w = -30 + 19 Combine like terms: -19 + 19 = 0 0 + 11w = -30 + 19 11w = -30 + 19 Combine like terms: -30 + 19 = -11 11w = -11 Divide each side by '11'. w = -1 Simplifying w = -1
| 10x+12=8x+4 | | 4x-7=3x-12 | | 5m+5.75=43.25 | | 8x-(600+2.50x)=1200 | | w-1/3=2 | | -x+5=x-11 | | 3b=20 | | 3x+1y=5 | | 8=2(w-2) | | -6u+7= | | 5+d=8d-7 | | 3/5c=2c-7 | | 9-q=5 | | 24/48=50/x | | x+y=10000 | | 12k-11k+2=16 | | 12-8(4-s)+3(s+3)=27 | | 3-2(x-5)=13 | | x(3+2)+9=2x-12 | | 8w+2w-2=18 | | 5c+12-3c=28 | | x-sqrt(40-3x)=0 | | 4x+5(3x-3)=6 | | 2m-4=10+18 | | x(x-3)(x+12)=324 | | 3x+6y=-9 | | 7x+4y=53500 | | 2m-4=10+16 | | F(t)=0.25t^2-0.5t+3.5 | | 26=-7x+5(x+8) | | c+4=3/4 | | 6x-(5x+4)=5x-32 |